競技経験のない一般女子学生のクロール泳における異なる速度による腹腔内圧および体幹筋活動の変化 - 金沢, 翔一; 森山, 進一郎; 柴田, 義晴; 北川, 幸夫 (体育測定評価研究, 2016)
The purpose of this study was to clarify the changes in intra-abdominal pressure (IAP) and trunk muscle activity during front crawl swimming at submaximal and maximal swimming velocities. Subjects were 10 female collegiate recreational swimmers. All subjects performed front crawl swimming at very slow, normal, and maximal velocities for 20m. Swimming velocity (V), stroke rate (SR), and stroke length (SL) were measured as swimming performance indices. In addition, the IAP and EMG of the rectus abdominis (RA), erector spinae (ES), and transversus abdominis – internal oblique (TrA-IO) were measured as indices of trunk muscle activity. IAP was taken as the difference between the minimum and maximum values, and EMG was reported as the mean of 2 stable front crawl stroke cycles measured as root mean square values. There were significant differences in V and SR among all velocities. However, there were no significant differences in SL, IAP, and RA. These results suggested that recreational swimmers increase their swimming velocity without co-contraction of the trunk muscles